INTERAKSI SOSIAL SISWA DALAM PEMBELAJARAN DARING - Muh. Ilham (Indonesian Journal of Educational Technology, 2023)
This article aims to provide an overview to students of the importance of social interaction when online learning is implemented at Makassar State University. The method used in the preparation of this article is descriptive-qualitative with a purposive sampling approach based on certain criteria so that the data obtained is in accordance with existing facts until it is known that, in terms of education, the application of online learning reduces the educational function for students due to reduced interaction, which results in reduced student learning quality such as lack of understanding of learning materials, communication that can be interrupted due to the network, or more interested in online games than the learning material itself. And in terms of family, online learning is able to strengthen the relationship between parents and children so that they can understand each other because of the frequent interactions that occur.